2022
DOI: 10.5005/jp-journals-10071-24086
|View full text |Cite
|
Sign up to set email alerts
|

Etomidate Compared to Ketamine for Induction during Rapid Sequence Intubation: A Systematic Review and Meta-analysis

Abstract: A bstract Aims and objectives The objective of the study was to compare the safety and efficacy of etomidate and ketamine as induction agents for rapid sequence intubation (RSI) in acutely ill patients in emergency department and prehospital settings with respect to post-induction hypotension and first-pass intubation success during RSI. Materials and methods For this systematic review and meta-analysis, we searched PubMed, Embase, Cochrane, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 23 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…In one study, propofol was found to independently increase mortality rates compared to midazolam as a procedural sedative in massive PE 37 . In the setting of rapid sequence intubation, ketamine and etomidate are both well-studied agents that may be chosen for their minimal hemodynamic effect, though recent literature has documented increased rates of hypotension with ketamine in patients who are already hemodynamically compromised before intubation, which is believed to be due to ketamine-induced exhaustion of catecholamine reserves 38,39 . For continuous sedation on mechanical ventilation, a benzodiazepine infusion again carries a milder risk profile in regards to heart rate and blood pressure but is associated with other complications such as prolonged time on the ventilator and delirium.…”
Section: Sedation Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, propofol was found to independently increase mortality rates compared to midazolam as a procedural sedative in massive PE 37 . In the setting of rapid sequence intubation, ketamine and etomidate are both well-studied agents that may be chosen for their minimal hemodynamic effect, though recent literature has documented increased rates of hypotension with ketamine in patients who are already hemodynamically compromised before intubation, which is believed to be due to ketamine-induced exhaustion of catecholamine reserves 38,39 . For continuous sedation on mechanical ventilation, a benzodiazepine infusion again carries a milder risk profile in regards to heart rate and blood pressure but is associated with other complications such as prolonged time on the ventilator and delirium.…”
Section: Sedation Strategiesmentioning
confidence: 99%
“…37 In the setting of rapid sequence intubation, ketamine and etomidate are both well-studied agents that may be chosen for their minimal hemodynamic effect, though recent literature has documented increased rates of hypotension with ketamine in patients who are already hemodynamically compromised before intubation, which is believed to be due to ketamine-induced exhaustion of catecholamine reserves. 38,39 For continuous sedation on mechanical ventilation, a benzodiazepine infusion again carries a milder risk profile in regards to heart rate and blood pressure but is associated with other complications such as prolonged time on the ventilator and delirium. Dexmedetomidine, a selective α2 agonist, is associated with shorter times to extubation and decreased rates of delirium when compared with benzodiazepine; however, it also carries the potential to cause profound hypotension and bradycardia through its anti-adrenergic effects.…”
Section: Sedation Strategiesmentioning
confidence: 99%
“…Nesse contexto, tem-se o etomidato, um hipnótico não barbitúrico de ação ultrarrápida e administração intravenosa utilizado para a indução na IOT (Williams;Boyd;Fitzgerald, 2023). O etomidato está associado à diminuição do risco de hipotensão pós-indução durante a intubação de sequência rápida (Sharda;Bhatia, 2022), mas ainda é importante compreender as nuances da aplicação deste fármaco em pacientes complicados.…”
Section: Introductionunclassified
“…Different anesthesia induction protocols are administered for this purpose. Etomidate and ketamine are potentially more suitable agents in terms of preventing hypotension, one of the problems that arise during anesthesia induction [3].…”
Section: Introductionmentioning
confidence: 99%